Impact of Coming Demographic Changes on the Number of Adults in Need of Care for Hypertension in Brazil, China, India, Indonesia, Mexico, and South Africa: A Modeling Study. Issue 4 (April 2019) - Sudharsanan, Nikkil; Geldsetzer, Pascal
Abstract : Over the coming decades, middle-income countries are expected to undergo substantial demographic changes. We estimated the consequences of these changes on the number of adults in need of hypertension care between 2015 and 2050 using nationally representative household-survey data collected in Brazil, China, India, Indonesia, Mexico, and South Africa (N=770 121). To reflect unmet need for healthcare, we defined hypertension as systolic blood pressure ≥140 mm Hg or diastolic blood pressure ≥90 mm Hg regardless of treatment status. Using a mathematical disease projection equation, we calculated the change in the number of individuals in need of hypertension care in each country that was due to changes in population size, age composition, and age-specific prevalence under various epidemiological scenarios. If the current age-specific prevalence schedule of hypertension remains unchanged until 2050, demographic changes alone will increase the number of adults in need of hypertension care by 319.7 million individuals, ranging from a relative growth of 55% in China to 151% in Mexico. Even if the age-specific prevalence of hypertension is reduced by 25% by 2050 among adults aged ≥40 years, the number of individuals in need of hypertension care will still increase by 145.9 million individuals, with relative increases ranging from 16% in China to 88% in Mexico. Overall, our results suggest that coming demographic changes in middle-income countries will overpower even ideal prevention efforts. Middle-income countries will need to massively expand healthcare services for aging-related diseases, such as hypertension, if they are to meet the virtually inevitable future increase in care needs for these conditions. Abstract : Supplemental Digital Content is available in the text.